Pyschopathy Traits: An Analysis Of Main Character In the Novel "Mine" by Siti Nur Atika - Hasna Nurain Mukhsin (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
Pyschopathy Traits: An Analysis Of Main Character In the Novel "Mine" by SitiNur Atika. A psychopath is a person with disordered psychology who hasdifficulties conforming to the social standards that exist in their surroundings.This study focused on the psychotic aspect of Sean, a character in Mine novel.The descriptive qualitative approach and Robert D. Hare's theory were utilized inthis study to uncover Sean's psychopathic features. The findings of this studyshow that Sean possesses five psychopathic characteristics. That is,mercilessness, possessiveness, shallow emotionality, lack of empathy, and asense of personal satisfaction.Keywords: Psychopathy, traits